The serine-threonine protein phosphatases that regulate the thiazide-sensitive NaCl cotransporter - Carbajal-Contreras, Héctor; Gamba, Gerardo; Castañeda-Bueno, María (Frontiers in Physiology, 2023)
The activity of the NaCl cotransporter (NCC) in the distal convoluted tubule (DCT) is finely tuned by phosphorylation networks involving serine/threonine kinases and phosphatases. While much attention has been paid to the With-No-lysine (K) kinase (WNK)- STE20-related Proline Alanine rich Kinase (SPAK)/Oxidative Stress Responsive kinase 1 (OSR1) signaling pathway, there remain many unanswered questions regarding phosphatase-mediated modulation of NCC and its interactors. The phosphatases shown to regulate NCC’s activity, directly or indirectly, are protein phosphatase 1 (PP1), protein phosphatase 2A (PP2A), calcineurin (CN), and protein phosphatase 4 (PP4). PP1 has been suggested to directly dephosphorylate WNK4, SPAK, and NCC. This phosphatase increases its abundance and activity when extracellular K+ is increased, which leads to distinct inhibitory mechanisms toward NCC. Inhibitor-1 (I1), oppositely, inhibits PP1 when phosphorylated by protein kinase A (PKA). CN inhibitors, like tacrolimus and cyclosporin A, increase NCC phosphorylation, giving an explanation to the Familial Hyperkalemic Hypertension-like syndrome that affects patients treated with these drugs. CN inhibitors can prevent high K+-induced dephosphorylation of NCC. CN can also dephosphorylate and activate Kelch-like protein 3 (KLHL3), thus decreasing WNK abundance. PP2A and PP4 have been shown in in vitro models to regulate NCC or its upstream activators. However, no studies in native kidneys or tubules have been performed to test their physiological role in NCC regulation. This review focuses on these dephosphorylation mediators and the transduction mechanisms possibly involved in physiological states that require of the modulation of the dephosphorylation rate of NCC.